2014
DOI: 10.1007/s11618-014-0546-x
|View full text |Cite
|
Sign up to set email alerts
|

Selection patterns, gender and friendship aim in classroom networks

Abstract: The social networks of students, and the underlying processes of selection, can have strong effects on their psychological and academic adjustment. The effects of gender, friendship aim (intimacy or social activities) and the combination of gender and friendship aim on selection patterns (student's activity in selecting new friends, linking with friends of friends, and similarity in behavior) were studied, using two wave data from 741 students (12-14 years old) in 27 freshmen classes in Dutch high schools.Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…With regard to gender differences, this study reveals that the number of bullies involved is especially important to boys’ psychosocial well-being and rejection by classmates. This is in line with research findings that boys tend to interact in groups where competition, and thus the number of opponents, plays an important role [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…With regard to gender differences, this study reveals that the number of bullies involved is especially important to boys’ psychosocial well-being and rejection by classmates. This is in line with research findings that boys tend to interact in groups where competition, and thus the number of opponents, plays an important role [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…As expected, more reporter-receiver agreement was found in same gender dyads, and in particular in boy-boy dyads. An explanation could be that children and early adolescents predominantly interact in peer groups of the same gender and, consequently, are more likely to have information about social interaction patterns within their peer groups than about social interactions involving peers of the other gender (Baerveldt et al, 2014;Rubin et al, 2006). Furthermore, an additional explanation for why greater reporter-receiver agreement was found in boy-boy dyads is that victimization among boys is perhaps easier to recognize than victimization among girls.…”
Section: Characteristics Of the Reporter-receiver Dyad And Of The Repmentioning
confidence: 99%
“…Even when reporters and receivers do not consider themselves as friends, it is plausible that they interact and share information with each other more often when they are similar than when they are dissimilar. Especially, similarity in gender might affect reporter-receiver agreement, because several studies have indicated that gender segregation is strong during childhood and early adolescence and that social interaction predominantly takes place in same-gender peer groups (Baerveldt, Van De Bunt, & Vermande, 2014;Rubin et al, 2006;Veenstra, Lindenberg, Munniksma, & Dijkstra, 2010). Therefore, it is likely that students in same-gender dyads will have more information about social interaction patterns within their own peer groups than about social interactions involving peers of the opposite gender.…”
mentioning
confidence: 99%
“…More importantly, the current studies provided initial evidence for interaction mechanisms behind friendship selection. Studies on friendship network selection have only recently started to empirically examine underlying interaction mechanisms (e.g., Baerveldt, Van de Bunt, & Vermande, 2014). Here, we unraveled one specific bonding mechanism by showing that similarity in extraversion predicted positive interaction quality in real-life social interactions, which, in turn, predicted a higher likelihood of friendship selection (Selfhout et al, 2010;Van Zalk & Denissen, 2015).…”
Section: Selectionmentioning
confidence: 74%